An Efforts to Overcome The Shortage of Human Resources for The Effective Organizational Performance - Sahidin, Riki Hikman; Nurhayati, Mafizatun; Sultan, Zulkifli (International Journal of Applied Management and Business, 2025)
This research aims to produce a formulating regarding Efforts To Overcome The Shortage Of Human Resources for The Effectiveness of Organizational Performance In The Riau Islands Animal, Fish, And Plants Quarantine Office. The research method used is a qualitative descriptive analysis approach of case studies. The results of the research show that there is an impact of a shortage of human resources but it does not effectively have an influence on the organizational performance of The Riau Islands Animal, Fish, And Plants Quarantine Office. The impacts that occur affect employee personnel, such as increased workload, longer working hours, multiple positions for certain personnel and high stress levels for employees who hold multiple positions. From the research results, it is concluded that the role of leaders in evaluating and monitoring is the key to success in maintaining organizational performance effectiveness. Apart from that, the use of technology or digitalization of services must be increased so that the problem of shortage of human resources can be resolved.